Workplace harassment against women in Pakistan: An Islamic perspective - Abdul Khaliq, Abida; Ali Mohamed, Ashgar Ali; Ahmad, Muhammad Hassan (Advanced Research Trentz, 2021)
Islam highlights the role of women not only in the household but also to engage in employment and business activities. It also protects women at the workplace by extending the societal norms that have been shunned for women. This paper shows a comprehensive view of the concept of workplace harassment and Islam while also clarifying some misconceptions.It quotes many exemplary Muslim women from Islamic history to elucidate the supporting role of Islam. However, the problems arise either through a lack of knowledge or over extension of Islamic values in case of women’s protection and family responsibilities. The holy scripture of Islam, Quran, emphasises many times the unique and ubiquitous role of women which is further accentuated by Prophet Muhammad (s.a.w.). Hence, it is found that, in Pakistan,the prime reason for workplace harassment with women can be underlined with either the cultural restrictions or the lack of implementation of existing laws. Accordingly, it is vital to endeavourin the implementation and enforcement of its existing laws for the protection of women from harassment in all aspects of their lives